Modelling of 35-d superorbital cycle of B and V light curves of IMXB HZ Her/Her X-1 - Kolesnikov, D. A.; Shakura, N.; Postnov, K. A.; Volkov, I. M.; Bikmaev, I. F.; Irsmambetova, T. R.; Staubert, R.; Wilms, Jörn; Irtuganov, E.; Golysheva, P. Yu; Shugarov, S. Yu; Nikolenko, I.; et al. (Monthly Notices of the Royal Astronomical Society, 2020)
The X-ray binary Her X-1 consists of an accreting neutron star and the optical component HZ Her. The 35-d X-ray superorbital variability of this system is known, since its discovery in 1972 by the Uhuru satellite and is believed to be caused by forced precession of a warped accretion disc tilted to the orbital plane. We argue that the observed features of the 35-d optical variability of HZ Her can be explained by free precession of the neutron star with a period close to that of the forced disc. The model parameters include (a) the X-ray luminosity of the neutron star; (b) the optical flux from the accretion disc; and (c) the tilt of the inner and outer edges of the accretion disc. A possible synchronization mechanism based on the coupling between the neutron star free precession and the dynamical action of non-stationary gas streams is discussed.
CRIS-Team WoS Importer:2020-12-04